Evaluation of plants used for the control of animal ectoparasitoses in Southern Ethiopia (Oromiya and Somali regions) - Eloff, Jacobus Nicolaas (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2007.